Issues and challenges in enhancing the English language performance among level 2 students at selected primary school: a case study / Harison Lailee Mohd Sahidol - Mohd Sahidol, Harison Lailee (2012)
This case study is about issues and challenges in enhancing the English language performance among level 2 students at a selected primary school. It is to find out what are the factors that contribute to the students’ inability to excel in English language subject and to examine strategies that teachers can engage in to improve the English performance at level 2. The case study was carried out at SK Jengka Pusat 2, Maran, Pahang Darul Makmur. It involved 175 students of level 2 at the respective school. There were 93 male students and 82 female students who participated in this case study. Besides that, there were 15 English language teachers involved in this case study including 2 native speakers. The native speakers are The English Mentors who are involved in “Program Penutur Jati” or Teaching English Language Literacy Program under the MBMMBI Policy or Uphold The National Language and Strengthen The English Language Policy. This is a qualitative case study where data of this study comes from surveys, interviews, observations and document analysis. The students and the English teachers participated in the surveys, the interviews and the observations. The document analysis is the data from the examination results of Level 2 students from the recent year and from the previous year. The findings of this case study have showed that, the strategies that organized by the school have contributed to improve the performance of English language subject. Cooperation, support and hard work from parents, school administrators and teachers, are the right move to overcome the problem.